Articulatory Features and Associated Production Models in Statistical Speech Recognition - Deng, Li (Computational Models of Speech Pattern Processing (NATO ASI Series), 1999)
A statistical approach to speech recognition is outlined which draws close parallel with closed-loop human speech communication schematized as a joint process of encoding and decoding of linguistic messages. The encoder consists of the symbolically-valued overlapping articulatory feature model and of its interface to a nonlinear task-dynamic model of speech production. A general speech recognizer architecture based on optimal decoding strategy incorporating encoder-decoder interactions is described and discussed.